Pengaruh Pengulangan Dan Lama Penyimpanan Terhadap Ketengikan Minyak Kelapa Dengan Metode Asam Thiobarbiturat (TBA) - Zikra Azizah; Roslinda Rasyid; Desi Kartina (Jurnal Farmasi Higea, 2016)
The research aims to determine the effect of repeat frying and duration of storage to rancidity coconut oil used thiobarbituric acid (TBA) method. The sample used were coconut oil with three different brands namely coconut oil A, B, dan C. The highest TBA number of samples coconut oil A, B, dan C was after three frying and 2 days of storage, TBA number was 0.879, 0.694, and 1.336 mg malonaldehyde/Kg sample. Based on data, can conclude samples coconut oil A, B dan C has under gone rancidity, but still below the maximum limit set by Badan Standarisasi Nasional (1991) was 3 mg malonaldehyde/Kg sample. The quality coconut oil A, B, dan C still below the maximum limit set by Badan Standarisasi Nasional (2013) such as acid number was 0.6 mg KOH/g, peroxide number was 2 meq/kg, saponification number was 196-206, iod number was 45-46, and free fatty acid was 0.3 %.